Senates, Unions, and the Flow of Power in American Higher Education - Kemerer, Frank R. (Canadian Journal of Higher Education, 1983)
This article draws on longitudinal survey research to examine the influence pro- files of senates standing alone on college campuses in the United States, as well as the influence profiles of coexisting senates and faculty unions. The article discusses the forces prompting a flow of power away from faculty deliberative bodies and speculates on the future of faculty senates as hard times came to American higher education.